Strategi pengembangan agribisnis Ulat Sutera Pemakan Daun Singkong di Kabupaten Malang - Mutiara, Farah; NH., Dwi Asnani (Faculty of Animal Science, Universitas Brawijaya, 2017)
Recently, the needs of silk in the world is about 2,000 tons per year still can not be fulfilled due to lack of silkworm productivity. Indonesia has potential to develop natural silk, its amount of production is not more than 500 tons per year. Therefore, in order to obtain maximum production results, it should be supported by feed sources should be sufficiently sustainable. Cassava leaves can be used as an alternative feed on the silkworm’s farming which is call Samia cynthia ricini. The availability of its feed sources is abundant and the quality is extremely good. This study aims to: 1) analyse the feasibility level of agribusiness in cassava leaves silkworm eaters in Malang district, 2) describe the best marketing strategy based on SWOT analysis. The method used in this research was economic feasibility analysis or cost-benefit analysis which used to identify benefit, NPV and IRR. The results of the research indicate that the silkworm farming is profitable, with profit at 21.753.000,- annually; with B/C ratio of 1,074, NPV value is at Rp 144.287.115,- for a up to 5 years of cash flows, and the IRR value is at 2,896%. The application of development strategy in cassava leaves silkworm eaters should be based on internal and external factor in SWOT analysis, S-O, S-T, W-O and W-T.